2018
DOI: 10.1186/s12884-018-1797-y
|View full text |Cite
|
Sign up to set email alerts
|

Construction and pilot test of a set of indicators to assess the implementation and effectiveness of the who safe childbirth checklist

Abstract: BackgroundThe World Health Organization (WHO) launched the “Safe Childbirth Checklist (SCC) Collaboration” in 2012. The SCC is designed to contribute to quality care by providing reminders of evidence-based practices for the prevention and management of the leading causes of maternal and neonatal morbidity and mortality. However, indicators to monitor the implementation and effectiveness of the SCC have not been defined. This study aimed to produce and pilot test a set of valid, reliable and feasible indicator… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 24 publications
0
5
0
Order By: Relevance
“… 41 , 43 , 46 - 52 , 57 , 62 - 65 Other condition specific indicator selection processes in the literature have also emphasised this approach or the absence of it. 19 , 80 - 82 Of note, Hilarion et al articulate that “…indicator development and their application should not be separated” (p. 99). 80 …”
Section: Discussionmentioning
confidence: 99%
“… 41 , 43 , 46 - 52 , 57 , 62 - 65 Other condition specific indicator selection processes in the literature have also emphasised this approach or the absence of it. 19 , 80 - 82 Of note, Hilarion et al articulate that “…indicator development and their application should not be separated” (p. 99). 80 …”
Section: Discussionmentioning
confidence: 99%
“…It was developed in the context of the Safe Childbirth Project (approval protocol number 1 562 300/2015), an initiative for the implementation of WHO SCC in hospitals in Brazil and Mexico, which was part of the ‘WHO SCC Collaboration’. The validation of indicators used in the project, 19 20 the descriptive baseline results 4 and the process of adapting the SCC for Brazil 21 have been previously published. The present study tests the hypothesis that the adapted SCC can improve the quality of care during childbirth, both in processes and clinical outcomes.…”
Section: Methodsmentioning
confidence: 99%
“…After training and a pilot study to validate the indicators in both hospitals, 19 20 the data were collected with a prospective review of medical records. The reliability of the instrument during the pilot study in Brazil 20 showed Kappa indices with substantial agreement (>0.76) for most indicators and, when not, adjustments were made for greater clarity.…”
Section: Methodsmentioning
confidence: 99%
“…The variables of interest included simple and composite indicators of GP based on the items contained in the SCC, which were converted into indicators and pilot tested in a previous study,16 and adverse event indicators, which were based on the standardised obstetric quality indicators proposed by Mann et al 17…”
Section: Methodsmentioning
confidence: 99%
“…In both Brazil and Mexico,16 a pilot study was performed to analyse the reliability of the instrument, reaching kappa indices with substantial agreement (>0.76) for most of the indicators; alternatively, adjustments were made to the instrument, aiming for greater clarity and reliability. The pilot study cases were not part of the main study.…”
Section: Methodsmentioning
confidence: 99%